Defect‐Modulated Transistors and Gas‐Enhanced Photodetectors on ReS2 Nanosheets. Issue 6 (18th January 2016) - Yang, Shengxue; Kang, Jun; Yue, Qu; Coey, J. M. D.; Jiang, Chengbao
Abstract : Sulfur vacancies are demonstrated to modulate the interlayer interaction and bandgap in ReS2 nanosheet transistors, influencing the current on/off ratio and mobility.